Pengaruh level pupuk nitrogen terhadap profil pertumbuhan pada hidroponik fodder jagung (Zea mays L) - Anifiatiningrum; Sapta Andaruisworo; Erna Yuniati; Nur Solikin; Ardina Tanjungsari; Moh. Mimbar Fauzi (Fakultas Pertanian Universitas Majalengka, 2025)
Hydroponic corn fodder is a forage crop derived from corn, cultivated in a water medium and mixed with nutrients to meet the plant's nutritional needs. The purpose of this study was to determine the effect of nitrogen fertilizer levels on the growth profile of hydroponic corn fodder (Zea mays). This research was conducted in the Field Laboratory of the Animal Science Study Program, Nusantara PGRI University Kediri, with observations on the growth profile of hydroponic corn fodder. This study used a Completely Randomized Design (CRD) with an experimental method consisting of 4 treatments and 5 replications. The data obtained were analyzed using Analysis of Variance, and if the test results showed differences, further testing was conducted using the Duncan Multiple Range Test (DMRT). The main treatments were different levels of nitrogen fertilizer application, namely concentrations P0 (0 ml/l), P1 (0.8 ml/l), P2 (1.6 ml/l), P3 (2.4 ml/l). The results showed that different levels of nitrogen fertilizer application did not have a significant effect (P>0.05) on plant height, had a significant effect (P<0.05) on leaf width, leaf length, and stem length, and had a highly significant effect (P<0.01) on stem diameter and number of leaves in hydroponic corn fodder. The research results showed that the growth profile, viewed from the morphology of the stem and leaves in hydroponic corn fodder, showed the best values with increasing N doses, with the best research results shown at the use of N fertilizer dose of 1.6 ml/l (P2). Increasing the level of nitrogen fertilizer can enhance leaf width, leaf length, number of leaves, stem length, and stem diameter